Effects of pinealectomy on the levels and the circadian rhythm of plasma homocysteine in rats - Baydas, G; Gursu, MF; Cikim, G; Canpolat, S; Yasar, A; Canatan, H; Kelestimur, H (Wiley, 2002)
Hyperhomocysteinemia is an independent cardiovascular risk factor. There are several factors including aging that contribute to the development of hyperhomocysteinemia. Nevertheless, the exact mechanisms causing this condition are still debated. We hypothesize that the age-related decrease in melatonin levels may be consequential in hyperhomocysteinemia. Recently, we found that plasma homocysteine (Hcy) levels are increased in pinealectomized (PINX) rats and melatonin reverses this increase. The aim of the present study was to determine if there is a circadian rhythm of plasma Hcy in rats and to examine the effect of pinealectomy on this cycle. Plasma Hcy levels demonstrated a 24-hr rhythm with a peak at 02:00 hr and a nadir at 14:00 hr in both control and PINX rats. Pinealectomy did not change the phase of the rhythm or the nocturnal elevation of plasma Hcy, but it did significantly increase mean plasma Hcy levels compared with those in controls and in rats that were sham pinealectomized (sPINX) (P < 0.05). Melatonin decreases plasma Hcy levels while causing an increase in total glutathione (tGSH). In conclusion, we speculate that decreasing levels of melatonin during aging lead to hyperhomocysteinemia and a decrease in tGSH and the latter may be one of the factors causing hyperhomocysteinemia in the elderly population.
Keywords: glutathione; Hcy; hyperhomocysteinemia; melatonin; pinealectomy